The U.S.-China Bilateral Trade Balance: It's Size and Determinants - Robert Feenstra; Wing Thye Woo; Wen Hai; Shunli Yao (University of California, Department of Economics, 1998)
This paper has two aims. The first is to reduce the range within which the true U.S.-China bilateral trade deficit lies. The second is to identify the determinants of the bilateral trade deficit, and offer an assessment of their relative importance. We calculate a smaller range of values for the bilateral trade deficit than in previous studies, due to a new estimation method that takes advantage of our access to detailed Chinese Customs data at the commodity level. For example, the revised U.S.-China bilateral trade deficit is 15 billion to 20 billion in 1994, and 16 billion to 22 billion in 1995, compared to the official range of 8 billion to 30 billion, and 9 billion to 34 billion, respectively. The widening of the U.S.-China bilateral trade deficit in recent years reflected many factors. In our opinion, the two chief factors are (i) macroeconomic forces in the U.S. and China moving in opposite directions, causing their respective overall trade balance to move in opposite directions; and (ii) the accelerated relocation of production of U.S. imports from East Asia to China.
Keywords: 330